Risk appetite and hedging strategies: the impact of age cohorts in financial markets - M. Aravind; C. G. Manojkrishnan (Cogent Economics & Finance, 2024)
The financial instruments are subject to market risk, and the degree of risk may differ. Numerous demographic and behavioral factors determine the willingness of retail investors to face market risk. This work examines the direct effect of investors' risk appetite on their risk mitigation strategies and the indirect effect of investors' risk appetite on hedging strategies through financial intermediaries. In both situations, the age cohort is fixed as a moderator. The data consists of 612 active stock market investors across India. The analysis has established partial mediation in the indirect path. The investors aged 26-40 appear to be risk-oriented, whereas those above 60 reported being risk-averse. These results show that risk appetite decreases with age, and people prefer stable returns to volatility as their age progresses. This research points to policymakers and intermediaries to design portfolio management services that fit the investors' age group. The purpose of this study is to examine whether the risk appetites (RA) of retail investors can have an impact on their hedging strategies (HS) in financial markets and how the age factor is influencing the risk aspiration of the investors. The mediation role of financial intermediaries (FI) in the risk mitigation process and how the service of financial intermediaries (FI) was availed of by investors across age cohorts were duly examined. The study results show that the young investors are more risk-oriented than the older ones and they prefer to rely on their own hedging strategies rather than the tips suggested by financial intermediaries. This result suggests that stock brokers and financial intermediaries must design a balanced decision-making board on the basis of the age group of the investors.
Keywords: 330; Risk appetite; financial intermediation; hedging strategies; mediated moderated analysis; age cohorts